2022
DOI: 10.1177/00986283211064339
|View full text |Cite
|
Sign up to set email alerts
|

We Need More Praxis: A Case for Praxis Assignments in Psychology Courses

Abstract: Introduction This paper explores what praxis is and its importance for catalyzing social justice. Statement of the Problem At times, psychologists have articulated the importance of bridging the researcher-activist divide via praxis, but progress in creating these bridges has been slow. Literature Review We examine how praxis can be rooted in decolonial pedagogical approaches and a tool that can bridge scholarship and activism. Building on previous work by teachers of psychology, we review small, medium, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…In a world of multiple and intertwined crises, preparing undergraduate students to address societal challenges should be a requirement for any course. Psychology has a key role to play in addressing the critical issues the world is currently facing (Kontopodis & Jackowska, 2019; Rosales & Majzler, 2023). For students, understanding and trialling how psychology can be applied to global and local challenges is vital to the development of psychological literacy (e.g., Cranney et al, 2022), and there is a need for innovative approaches that help prepare them to work with others in finding solutions for current and future societal challenges.…”
Section: Introductionmentioning
confidence: 99%
“…In a world of multiple and intertwined crises, preparing undergraduate students to address societal challenges should be a requirement for any course. Psychology has a key role to play in addressing the critical issues the world is currently facing (Kontopodis & Jackowska, 2019; Rosales & Majzler, 2023). For students, understanding and trialling how psychology can be applied to global and local challenges is vital to the development of psychological literacy (e.g., Cranney et al, 2022), and there is a need for innovative approaches that help prepare them to work with others in finding solutions for current and future societal challenges.…”
Section: Introductionmentioning
confidence: 99%
“…The results of Hicks, Alvarez, and Domenech Rodríguez's (2023) study with students in a multicultural psychology course indicated that incorporating a component involving difficult dialogues was associated with higher social justice behavioral intentions and perceived behavioral control than the comparison group pre to post. Rosales and Majzler (2023) offer various assignments to increase praxis; engaging students in cycles of deep critical thinking and transformative action.…”
Section: Introductionmentioning
confidence: 99%